Kinematic and morphometric assessment of fresh semen, before, during and after mating period in brahman bulls - Araya-Zúñiga, Ignacio; Molina-Montero, Rafael; Sevilla, Francisco; Roldan, Eduardo R. S.; Barrientos-Morales, Manuel; Silvestre, Miguel A.; Valverde-Abarca, Anthony (Animals, 2024)
The objective of the present study was to determine the effects that the reproductive season has on the motility, kinematics, morphology, and sperm morphometry of Brahman bulls evaluated with a commercial CASA system. The experiment was carried out at the Costa Rica Institute of Technology from March to August 2021. A total of eight Brahman bulls were used. A total of 28 ejaculates were collected in the pre-mating period (PMP), during it (DMP), and after it (AMP) using an electroejaculator. The sperm concentration was measured with the Accuread photometer. The motility was measured using a Spermtrack® counting chamber. The analyses were performed with the CASA-Mot ISAS®v1 system. The morphology was analyzed using a microscope with a negative phase contrast objective. Morphometry was evaluated with the CASA-Morph. The sperm concentration did not present differences between the PMP and AMP; however, it was significantly higher than DMP (p > 0.05). Regarding the progressiveness variables, linearity on forward progression (LIN), straightness (STR), and wobble (WOB) were higher (p < 0.05) DMP. A kinematic principal component analysis grouped all the variables into three factors and an effect on the reproductive period was found (p < 0.05) in the parameters of the head and middle part of the sperm, such as width and perimeter, which were greater in the PMP. The length of the sperm head in the PMP and DMP did not show differences; however, both were larger (p < 0.05) than AMP. The insertion distance of the middle piece of the sperm was significantly greater than DMP. Finally, the PMP contained cells with a larger insertion angle (p < 0.05) than AMP. These findings are important to understand the implications of reproductive status on sperm quality and to consider them in andrological evaluations.
Animals, vol.14, no.132 (Dec, 2024)
Keywords: Cerdos; Reproducción animal; Inseminación artificial; Espermatozoides; Nutrición animal; Espermatozoides-Motilidad; Casa - Programa para computador